Bacterial synthesis of phtocatalytically active and biocompatible TiO2 and ZnO nanoparticles - Singh, Sanjay; Britto, Virginia D.; Bharde, Atul A.; Sastry, Murali; Dhawan, Alok; Bhagavatula L. V. Prasad (International Journal of Green Nanotechnology: Physics and Chemistry, 2010)
TiO2 and ZnO nanoparticles are well known for their photocatalytic and ultraviolet (UV)-absorbent properties and have successfully entered into the market as consumer products. Large volume production of these nanoparticles by industries require environmentally friendly processes of synthesis. In this article, we show that when challenged with an appropriate precursor, the bacterium Actinobacter spp. can lead to the extracellular synthesis of ZnO and TiO2 nanoparticles. The biological way of synthesizing these materials probably leads to the in situ doping of elements like C, F, and N into their crystal lattices, which is evidenced by a red shift in the absorption edge. Because the doping is expected to affect the photocatalytic activity of these materials under different light conditions, such investigations have also been undertaken here. Further, the biocompatibility of these nanomaterials (cytotoxicity and genotoxicity) has also been investigated in detail.
Keywords: Biosynthesis; genotoxicity; Nanoparticles; Nanotoxicity; Photocatalysis

Heterofunctional nanomaterials: fabrication, properties and applications in nanobiotechnology - Kumar, S. Anil; Khan, Mohammad Islam (Journal of Nanoscience and Nanotechnology, 2010)
Nanotechnology and nanoengineering includes a novel class of materials that are gaining significant recognition to pursuit technological/biological advances in diverse fields including, biology, medicine, electronics, engineering etc. due to their unique size- and shape-dependent intrinsic physicochemical, optoelectronic and biological properties. Characteristics such as high surface to volume ratios and quantum confinement results in materials that are qualitatively different from their bulk counterparts. These properties not only make them suitable for numerous applications in existing and emerging technologies, but also have outstanding role in many fields that provide inspiration for their fabrication. In Today's trend nanotechnology is spreading vigorously where researchers all over the world are focusing towards their synthesis and applications. Therefore, this review is helpful for the researchers in the field of nanobiotechnology/nanomedicine, providing a brief overview of nanotechnology, covering nanomaterial synthesis methods (with emphasis on environmentally benign greener approaches), their properties, and applications; such as drug delivery, bio-labeling, nanotoxicity etc. The influence of synthesis methods and surface coatings/stabilizing agents and their subsequent applications is discussed, and a broad outline on the biomedical applications into which they have been implemented is also presented.
Keywords: Bio-Fabrication; Bio-Labeling; Cell imaging; drug delivery; Greener Synthesis; Nanomaterials; Nanotoxicity